KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KEMAMPUAN PROFESIONAL GURU PADA SMA NEGERI 2 PULO ACEH ACEH BESAR. - Saifullah, Cut Zahri Harun, Yusrizal. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Managerial competence will be very determining toward the advancement of educational institution. A good managerial competence of principal will help improving professionalism of teachers in order to improve the quality of education in State Senior High School (SMA Negeri ) 2 of Pulo Aceh of Aceh Besar. This study aimed to describe the managerial program, the implementation of managerial competence, and the professionalism of teachers in SMA Negeri 2 of Pulo Aceh. To achieve the aim, this study used qualitative approach with descriptive method. The techniques of data collection were observation, interview, and documentation study. The procedures of data analysis were data reduction, data display, and data verification. The subjects of the study were principal, vice principal, and teachers. The result of the study showed that: (1) the principal of SMA Negeri 2 of Pulo Aceh had the skill to encourage staffs, teachers, and employees, optimize the school resources, guide students, and give good model in teaching. The principal has been fully responsible in advancing the school. The attitudes were patient, careful, work hard, and discipline. Therefore, the principal has tried to put himself as a leader that suited the expectation of teachers and other related stakeholders, that the principal had already had managerial programs in improving professionalism of teachers. (2) The principal in improving professionalism of teachers gladly accepted advices and critiques from his subordinates and communicated the policies and problems together. (3) The obstacles faced by the principal in implementing managerial program to improving professionalism of teachers were the inadequate of numbers of teachers and the lack of facilities and infrastructure to support the educational process.Keywords: Managerial Competence, Principal, and Professionalism of TeacherAbstrak: Kompetensi manajerial akan sangat menentukan terhadap kemajuan suatu lembaga pendidikan. Apabila kompetensi manajerial kepala sekolah baik, maka akan mampu meningkatkan kemampuan profesional guru dalam meningkatkan mutu pendidikan di SMA Negeri 2 Pulo Aceh Aceh Besar. Penelitian ini bertujuan mendesripsikan program manajerial, pelaksanaan kemampuan manajerial, dan hambatan dalam pelaksanaan manajerial oleh kepada sekolah dalam meningkatkan kemampuan profesional guru di SMA Negeri 2 Pulo Aceh. Untuk mencapai tujuan tersebut, penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui: Observasi, Wawancara dan Studi Dokumentasi. Prosedur analisis data adalah Reduksi Data, Display Data, dan Verifikasi data. Sedangkan subjek penelitian adalah: Kepala Sekolah, Wakil Kepala Sekolah dan Guru. Hasil penelitian menunjukkan bahwa: (1) Kepala sekolah SMA Negeri 2 Pulo Aceh memiliki kemampuan menggerakkan staf, guru, dan karyawan, mengoptimalkan sumber daya sekolah, serta memiliki kapasitas membimbing siswa, serta mampu memberi contoh mengajar yang baik. Kepala sekolah telah bertanggungjawab penuh dalam memajukan sekolah. Sikap yang telaten, hati-hati, giat bekerja, dan disiplin waktu. Dengan demikian, kepala sekolah telah berusaha menempatkan dirinya sebagai pemimpin yang sesuai dengan harapan para guru dan semua pihak yang terkait, sehingga kepala sekolah sudah memiliki program manajerial dalam meningkatkan profesional guru. (2) Kepala sekolah dalam meningkatkan pelaksanaan kemampuan profesional guru, meningkatkan profesional dan senang menerima saran dan kritik dari bawahan, serta mengkomunikasikan kebijakan dan masalah secara bersama, dan (3) Hambatan kepala sekolah dalam pelaksanaan manajerial untuk meningkatkan kemampuan profesional guru berupa: gurunya belum mencukupi dan masih kurangnya sarana dan prasarana penunjang kelancaran proses pendidikan.Kata kunci: Kompetensi Manajerial, Kepala Sekolah, dan Profesional Guru.